Implementasi Sistem Informasi Kesehatan Daerah (SIKDA) Generik Guna Menunjang Efektivitas Rekam Medis Elektronik di UPTD Puskesmas Campaka - Rian Rusmana; Irda Sari (Politeknik Negeri Jember, 2023)
The enactment of Minister of Health Regulation Number 24 of 2022 concerning Medical Records has had a significant impact on health facilities, especially puskesmas, which are first-level health facilities required to hold Electronic Medical Records (EMR). A health information system integrated with the SATUSEHAT platform is needed to support the implementation of electronic medical records. Generic SIKDA is very important starting from the collection, recording, processing, and dissemination of health information. This study aims to determine the implementation of Generic SIKDA to support the effectiveness of electronic medical records at UPTD Campaka Health Center. This research uses qualitative methods. Data collection by observation, interviews and documentation. However, there are still some shortcomings, such as lack of trained human resources, lack of infrastructure, slow development and renewal of SIKDA Generic, and poor governance. In this case, SIKDA Generic has not been able to support Electronic Medical Records at UPTD Campaka Health Center.